Therapeutic potential of microRNA-506 in cancer treatment: mechanisms and therapeutic implications - Mao, Shuzhen; Li, Junyan; Huang, Jiahui; Lv, Lili; Zhang, Qilian; Cheng, Qing; Liu, Xiaojing; Bi, Zhiwei; Yao, Jing (Frontiers in Oncology, 2025)
Cancer is a complex and highly lethal disease marked by unchecked cell proliferation, aggressive behavior, and a strong tendency to metastasize. Despite significant advancements in cancer diagnosis and treatment, challenges such as early detection difficulties, drug resistance, and adverse effects of radiotherapy or chemotherapy continue to threaten patient survival. MicroRNAs (miRNAs) have emerged as critical regulators in cancer biology, with miR-506 being extensively studied and recognized for its tumor-suppressive effects across multiple cancer types. This review examines the regulatory mechanisms of miR-506 in common cancers, focusing on its role in the competing endogenous RNA (ceRNA) network and its effects on cancer cell proliferation, apoptosis, and migration. We also discuss the potential of miR-506 as a therapeutic target and its role in overcoming drug resistance in cancer treatment. Overall, these insights underscore the therapeutic potential of miR-506 and its promise in developing novel cancer therapies.